2017
DOI: 10.3390/ijms18051031
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of Cerebral Blood Flow during Severe Hypovolemia and Reperfusion in a Sheep Model: Critical Role of α1-Adrenergic Signaling

Abstract: Background: Maintenance of brain circulation during shock is sufficient to prevent subcortical injury but the cerebral cortex is not spared. This suggests area-specific regulation of cerebral blood flow (CBF) during hemorrhage. Methods: Cortical and subcortical CBF were continuously measured during blood loss (≤50%) and subsequent reperfusion using laser Doppler flowmetry. Blood gases, mean arterial blood pressure (MABP), heart rate and renal blood flow were also monitored. Urapidil was used for α1A-adrenergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 44 publications
(81 reference statements)
1
15
0
Order By: Relevance
“…Sheep were elected as the experimental model for our studies because of their similarities to humans, including body weight, physiological parameters, and organization of the brain. Using this model, we have previously shown that hemorrhage [20] or hypoxia [19], respectively, trigger differential CBF responses in the cortex and subcortex. Both damage models resulted in lower cortical CBF in comparison with subcortical CBF, which was replicated in this present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sheep were elected as the experimental model for our studies because of their similarities to humans, including body weight, physiological parameters, and organization of the brain. Using this model, we have previously shown that hemorrhage [20] or hypoxia [19], respectively, trigger differential CBF responses in the cortex and subcortex. Both damage models resulted in lower cortical CBF in comparison with subcortical CBF, which was replicated in this present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was a significant difference in the RBF response during reperfusion and recovery between the groups (p < 0.05, Figure 5D)-baseline RBF was only restored in serelaxin-treated animals. In control animals, hypovolemia (50% blood loss) had a differential effect on cortical and subcortical CBF [20]; baseline levels of cortical CBF were maintained up to a blood loss of 10%, but cortical CBF subsequently decreased to 41% ± 8% of the baseline value (p < 0.001, Figure 6A). In contrast, subcortical CBF remained constant up to 20% blood loss, with a subsequent decrease to 83% ± 6% of the baseline value at 50% blood loss (p < 0.001, Figure 6A).…”
Section: Effects Of Hypovolemia On Cbf and Vital Parametersmentioning
confidence: 99%
“…All animals remained under general anesthesia for the entire duration of the experiment and did not experience any pain or distress. The anesthesia and the surgical approach protocol were described previously [ 21 , 24 ]. Briefly, anesthesia was started by intramuscular injection of 10–15 mg·kg−1 ketamine (Ketamin-Hydrochlorid®, Pfizer, Berlin, Germany) and 0.2 mg·kg−1 midazolam (Midazolam-Hameln®, Hameln Pharmaceuticals, Hameln, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, in the rat carotid artery α1D-receptor signalling is involved in relaxation [ 19 , 20 ]. In previous studies we used sheep as an animal model, which are a convenient choice because of their similarity to humans in regard to body weight, blood volume and cerebral anatomy (such as gyration and vascular supply) [ 21 , 22 ]. These previous investigations revealed the redistribution of CBF during severe blood loss and subsequent reperfusion to be critically dependent on the activity of α1A-adrenergic receptors.…”
Section: Introductionmentioning
confidence: 99%
“…While the cerebral autoregulation protects the oxygen and energy supply of neuronal cells during physiologic blood pressure fluctuations [ 8 ], severe hypovolemia caused by haemorrhagic shock exceeds the cerebral autoregulatory capacity [ 9 ], which causes malperfusion and neuronal damages [ 10 ]. Further investigations suggest that cerebral cortical structures are more susceptible to sustain damages during the aforementioned states as compared to the subcortex [ 11 , 12 , 13 ]—whether this is due to an inherent higher vulnerability on the cellular level as compared to the subcortex, or whether subcortical structures are better protected at the lower limits of the cerebral autoregulation, is still unclear. Since the cerebral cortex is essentially the centre of human cognition and thereby responsible for the enactment of adequate social responses to exterior influences [ 14 ], cortical damages often negatively influence the patients’ ability to return to work and maintain or return to the previously lived lifestyle.…”
Section: Introductionmentioning
confidence: 99%